Dr. William Watfa — Deep Plane Facelift — Beirut - Watfa, William (DEEPPLANE™, 2026)
Surgeon profile record for Dr. William Watfa, practicing in Beirut, Lebanon. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003077; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; lebanon; beirut